Comparison of outcomes between video laryngoscopy and flexible fiberoptic bronchoscopy for endotracheal intubation in adults with cervical neck immobilization: A systematic review and meta-analysis of randomized controlled trials. - Nana Guo; Xuxin Wen; Xiao Wang; Junling Yang; Haidong Zhou; Jianli Guo; Yun Su; Tingxin Zhang (PLoS ONE)
Purpose Comparing the outcomes of video-laryngoscopy and flexible fiberoptic bronchoscopy for endotracheal intubation in patients with cervical spine immobilization. Methods All of the comparative studies published in the PubMed, Cochrane Library, Medline, Web of Science, and EMBASE databases as of 8 Jan 2024 were included. All outcomes were analyzed using Review Manager 5.4. The primary outcomes were the successful first-attempt intubation rate, intubation time, heart rate after intubation, mean arterial pressure after intubation, overall intubation success rate, risk of tissue damage and sore throat. Results The meta-analysis included six randomized controlled studies with a total of 694 patients. The outcomes of the meta-analysis revealed that the use of video laryngoscopy was better than flexible fiberoptic bronchoscopy in terms of the successful first-attempt intubation rate (P<0.05) and intubation time (P<0.05) in patients with cervical spine immobilization. However, there were no statistically significant differences in heart rate after intubation, mean arterial pressure after intubation, overall intubation success rate, risk of tissue damage, or sore throat (all P>0.05) between the video laryngoscopy and flexible fiberoptic bronchoscopy groups. Conclusions Compared with flexible fiberoptic bronchoscopy, video laryngoscopy has superior tracheal intubation performance in terms of the first-attempt success rate and intubation speed. This finding was observed in patients with cervical spine immobilization who utilized a cervical collar to simulate a difficult airway. Additionally, both types of scopes demonstrated similar complication rates. Current evidence suggests that video laryngoscopy is better suited than flexible fiberoptic bronchoscopy for endotracheal intubation in patients immobilized with a cervical collar. Trial registration Systematic review protocol: CRD42024499868.